Effects of environmental art perception on students’ creativity and emotional development - Sun, Yuanyuan; Liu, Shunli (International Journal of Evaluation and Research in Education (IJERE), 2024)
Addressing the gap in understanding how environmental art perception (EAP) and emotional development (ED) influence creativity among fine arts college students, this study focuses on their interrelations in China’s Henan Province. The objective is to investigate the effects of EAP and ED on creativity within this demographic. Employing a survey method, the study gathered data from 585 students across comprehensive art colleges in Henan Province, analyzing the impact of campus art design on creativity and the mediating role of ED. The findings reveal that EAP significantly enhances creativity, with campus art design playing a crucial role. Furthermore, ED serves as an essential mediator, fostering creativity through improved emotional awareness, expression, and management. Based on these insights, the study recommends educational strategies that integrate ED with the cultivation of creative thinking. Such approaches aim to nurture art professionals who not only excel in creativity but also in emotional intelligence, emphasizing the need to optimize environmental art exposure and focus on emotional skills in art education.